Autorzy:Alina Przychoda, Zygmunt Łaszczyk
Wydawnictwo:WSiP
Rok wydania:2015
Oblicz wartość wyrażenia dla x=-3/4 i y=-1/3.4.6 gwiazdek na podstawie 5 opinii

a)

`12x^2y-7xy=12*(-3/4)^2(-1/3)-7*(-(strike3)/4)*(-1/(strike3))=strike12*9/(strike16)(-1/3)-7*(-1/4)*(-1/1)=`

`=strike3*9/4*(-1/(strike3))-7*1/4=-9/4-7/4=-16/4=-4`

b)

`3x^2-2y^2=3*(-3/4)^2-2*(-1/3)^2= 3*9/16-2*1/9=27/16-2/9= (27*9)/144-(16*2)/144=`

`=243/144-32/144=211/144= 1 67/144`

c)

`4xy+2x^2-3y^2=4*(-(strike3)/4)*(-1/(strike3))+2*(-3/4)^2-3*(-1/3)^2= strike4*(-1/(strike4))(-1)+strike2*9/(strike16)-strike3*(1/(strike9))=`

`=1+9/8-1/3=1+1 1/8-1/3= 2 3/24-8/24=1 19/24` 

d)

` -1/2(xy^2)=-1/2*(-3/4*(-1/3)^2)=-1/2*(-strike3^1/4*1/strike9^3)=-1/2*(-1/12)=1/24`